A novel approach to suicide prevention – Educating when it matters - Desai, Nimisha D. (Ind Psychiatry J, 2018)
BACKGROUND: Looking at the burden of suicide, there is a dire need for medical schools to incorporate suicide prevention training. Effective communication helps in early detection and management of suicidal behavior. Medical students can act as a GATEKEEPER if they receive adequate training. METHODOLOGY: This was an educational intervention study done at tertiary care teaching hospital to assess the knowledge and attitude of medical students toward depression and suicide and to impart and assess communication skills for suicide prevention in one of the four batches of students in 4(th) semester. Pretest was conducted to assess knowledge and attitude toward depression and suicide, followed by training using interactive lectures, demonstration of interview, and hands-on training with patients and role-plays. The posttest and objective structured clinical examination (OSCE) were administered for skill assessment. Feedback was taken regarding this intervention. RESULTS: The mean marks of the pre- and post-test were 8.96 (8.3–9.6) and 14.58 (13.8–15.3), respectively, out of 25. The difference was statistically significant (t = 13.24, P ≤ 0.0001) which suggests improvement in knowledge. We found mixed responses in attitude statements showing limited change. Mean obtained marks on OSCE examination out of 66 was 42.7. Among various components of OSCE, students scored high on rapport building. The most useful components of trainings were role-play, OSCE, and interaction with patients as per their feedback. CONCLUSION: The intervention was found effective in increasing knowledge, changing attitude, and enhancing communication skills of medical students toward suicide prevention. Training of communication skills for suicide prevention in depressed person should be given to every medical student as suggested by feedback.